Pengabdian Masyarakat Berbasis Lingkungan melalui Pembangunan Taman Eco Green di Desa Taman Sareh Omben Sampang - Kurniawan, Yayak; Desiyanto, Jatim; Bariqoh, Asri (EDUPEDIA Publisher, 2025)
Community Service Program (KKN) is a form of student service to the community that integrates theory with practice in the field. The KKN program in Taman Sareh Village was implemented to address the issue of declining environmental quality due to the reduction of green open spaces and increased development activities. The solution offered is the construction of Eco Green Park as a green open space that has ecological, social, and educational functions. The main objectives of this activity are to improve environmental quality, raise public awareness of the importance of biodiversity, and encourage community involvement in environmental conservation. The implementation methods included preparation (condition analysis, socialization, location determination), implementation (land clearing, planting of 25 types of native plants, and maintenance training), and maintenance (watering, fertilizing, and routine evaluation). The results of the activity showed an improvement in air quality, an increase in local biodiversity, and the creation of a space for social interaction that strengthened community cohesion.In addition, the park serves as an educational tool for residents and students on the importance of greening. Despite facing obstacles such as limited types of adaptive plants and pest infestations, the program still managed to achieve its main objectives. Thus, the development of Eco Green Park can serve as a model for community-based environmental management to support sustainable village development.